Preparation and application of quick hemostatic gauze based on biomimetic mineralized thrombin. (6th August 2021) - Shi, Yuting; Ding, Xiaoquan; Cao, Yufei; Zhou, Haicun; Yu, Wenwen; Liu, Mingsheng; Yin, Juanjuan; Liu, Hongbin; Wang, Jingjing; Huang, Congshu; Gong, Chenliang; Wei, Hua; et al.
Abstract : This work aims to prepare ion/thrombin hybrid microflowers and thrombin/MOF by means of different biomineralization methods to improve the instability, bioavailability and poor storage stability of thrombin. Abstract : Thrombin is a serine protease known as activated coagulation factor II and is primarily applied as an effective local hemostatic agent. However, its clinical application is hindered by drawbacks, such as high sensitivity to the surrounding environment, instability and poor storage stability, easy inactivation, and low bioavailability. The biological functions of biomacromolecules in harsh environments can be preserved through biomineralization. Despite the success of biomimetic mineralization, limited consideration has been given to the mineral-based methods and the effect of various metal ions on enzyme activity. To explore an efficient technique for biomimetic mineralized thrombin, six kinds of ion/thrombin hybrid microflowers and two kinds of thrombin/MOF were synthesized in this work. The results showed that Zn-HNFs-G exhibits good hemostatic effect and maintains high enzymatic activity when exposed to high-temperature conditions. Meanwhile, Fe-HNFs-G, Thrombin@ZIF-8-G and Thrombin@MAF-7-G possess negligible enzyme protection.